ANALISIS SEKTOR EKONOMI POTENSIAL DI KOTA BAUBAU DENGAN MENGGUNAKAN PENDEKATAN BCG - Rahman, Rajab Abdul (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
The research objective is to analyze potential economic sectors in Baubau City through the BCG approach. This type of research is a descriptive research method with a quantitative approach. The type of data in this study is secondary data, namely data obtained through reference books, newspapers, journals and other documentation related to the focus discussed in this study. Data sources used in this study are the Central Statistics Agency (BPS) and the Baubau City GRDP 2013-2017. The analytical tool used in this study is LQ analysis. Next, after the shift share analysis is done, the last step using the Boston Consulting Group (BCG) method is a private management consulting company based in Boston. Boston Consulting Group is a company engaged in the development of market share. BCG was developed and popularized first by a leading management consultant. The results showed that the leading sectors to be developed in Baubau City using LQ analysis obtained results, namely: Agriculture, Trade, restaurants and hotels, Transportation and Communications and Services, were 4 potential sectors